A systematic review of depression psychotherapies among Latinos. (April 2016) - Collado, Anahí; Lim, Aaron C.; MacPherson, Laura
Abstract: For decades, the literature has reported persistent treatment disparities among depressed Latinos. Fortunately, treatment development and evaluation in this underserved population has expanded in recent years. This review summarizes outcomes across 36 unique depression treatment studies that reported treatment outcomes for Latinos. Results indicated that there was significant variability in the quality of RCT and type/number of cultural adaptations. The review suggested that there might a relation between cultural adaptations with treatment outcomes; future studies are warranted to confirm this association. Cognitive Behavioral Therapy was the most evaluated treatment (CBT; n  = 18, 50% of all evaluations), followed by Problem Solving Therapy (PST; n  = 4), Interpersonal Therapy (IPT; n  = 4), and Behavioral Activation (BA; n  = 3). CBT seems to fare better when compared to usual care, but not when compared to a contact-time matched control condition or active treatment. There is growing support for PST and IPT as efficacious depression interventions among Latinos. IPT shows particularly positive results for perinatal depression. BA warrants additional examination in RCT. Although scarce, telephone and in-home counseling have shown efficacy in reducing depression and increasing retention. Promotora -assisted trials require formal assessment. Limitations and future directions of the depression psychotherapy research among Latinos are discussed. Highlights: Historically, depressed U.S. Latinos have experienced treatment disparities. The review summarizes 35 studies that reported depression outcomes among Latinos. There is growing support for PST; CBT data appear mixed. RCT quality and number/type of cultural adaptations showed heterogeneity. Limitations and future directions of the literature are discussed.